Implementation of Code Switching in Titan Tyra’s Youtube Videos (A Sociolinguistics Study) - Clara Olivia Triverani Shantya Putri; Ervina CM Simatupang (Budapest International Research and Critics University, 2022)
This research entitled “Implementation of Code Switching in Titan Tyra’s YouTube Videos”. The researcher choose four videos from Titan Tyra’s YouTube channel as the data sources. The purposes of this research are:(1) to identify types of code-switching that appeared on Titan Tyra’s YouTube video, (2) to identify several factors that influence Titan Tyra to use code-switching. This research used qualitative method according to Strauss and Corbin (2007). The theories use to analyze the data were taken from Poplack (1980), Holmes (2013), and Myers (2006). The results of this research are 30 data and this is divided into 18 data of Inter-Sentential (60%), 6 data of Intra-Sentential (20%), and 6 data of Tag Switching (20%), while for the factor devided into 5 data of social context (12.5%), 5 data of the setting (12.5%), 8 data of the function (35%), 4 data of the topic (11%), 6 data of the participant (20%), and 3 data of cultural borders (9%). The most dominant type that appeared on Titan Tyra’s YouTube video is Inter-Sentential Switching, while the most dominant factor is the function because the language switch used by Titan Tyra only serve to explain and complete the meaning of her speech.